Effects of Linear Versus Changes of Direction Repeated Sprints on Intermittent High Intensity Running Performance in High-level Junior Football Players over an Entire Season: A Randomized Trial - Edvard H Sagelv; Ivar Selnæs; Sigurd Pedersen; Svein Arne Pettersen; Morten B Randers; Boye Welde (MDPI AG, 2019)
Background: Changes of direction (COD) repeated sprints (RSs) might have greater relevance to football than linear RSs. We aimed to compare the effects of linear and COD RSs on intermittent high intensity running (HIR) over an entire season. Methods: In total, 19 high-level male football players (16−19 years) randomly performed linear RSs or COD RSs twice a week during their competitive season over 22 weeks. Yo-Yo intermittent recovery test level 2 (Yo-Yo IR2), and 10- and 20-m sprint was assessed pre-, mid- (11 weeks), and post-intervention (22 weeks). Maximal oxygen uptake (VO2max) was assessed pre- and post-intervention. Results: There was no interaction effect (time x group) in Yo-Yo IR2 (p = 0.36, pη2 = 0.06) or sprint tests (10 m: p = 0.55, pη2 = 0.04, 20 m: p = 0.28 pη2 = 0.08), and no change differences between groups. There was a main effect of time for Yo-Yo IR2 (p = 0.002, pη2 = 0.31) but not in sprints or VO2max. Conclusion: Linear and COD RS exercise twice a week over 22 weeks equally improves intermittent HIR performance but does not improve sprint time or aerobic power in high-level junior football players. However, due to our two-armed intervention, we cannot exclude possible effects from other exercise components in the players’ exercise program.